Hydrolysable carbohydrate data collected from the trace metal rosette in the Southern Ocean during the austral summer of 2016/2017, on board the Antarctic Circumnavigation Expedition. - Hassler, Christel (Zenodo, 2020)
Dataset abstract Hydrolysable carbohydrate (referred to as TPZT from the analytical methodology used) is part of the labile pool of dissolved organic carbon that is excreted by most (micro)organisms or released by continental margins/sediments. It is a carbon source for heterotrophic bacteria. These carbohydrates could also potentially bind iron and act as an iron binding ligand. This data is used to explore the nature of iron ligands and relate to biological and chemical oceanography. Dataset contents ace_hydrolysable_carbohydrates_tpzt_data.csv, data file, comma-separated values ace_hydrolysable_carbohydrates_tpzt_data_visual_summary.png, metadata, portable network graphics README.txt, metadata, text format data_file_header.txt, metadata, text format change_log.txt Dataset license This hydrolysable carbohydrate dataset from ACE is made available under the Creative Commons Attribution 4.0 International License (CC BY 4.0) whose full text can be found at https://creativecommons.org/licenses/by/4.0/ Change log v1.1 - permissions changed to open access (CC BY 4.0 license) and small changes add license to README.txt format of data_file_header.txt add Frictionless Data schema files v1.0 - initial release of dataset : The Antarctic Circumnavigation Expedition was made possible by funding from the Swiss Polar Institute and Ferring Pharmaceuticals. This work was also supported by Swiss National Science Foundation grants PP00P2_138955 and PP00P2_166197. : {"references": ["Myklestad S, Sk\u00e5n\u00f8y E, Hestmann S, A sensitive and rapid method for analysis of dissolved mono- and polysaccharides in seawater. Mar Chem 56:279\u2013286 (1997)", "Ocean Data View (ver. 4.5). Schlitzer,R.(2012). OceanData View (version4.5)"]}